Analisis Kelayakan dan Strategi Pengembangan Usaha Sagu Lempeng (Study Kasus di Desa Siri Sori Serani) - Yuliana Leleulya; Stephen F.W Thenu; Raihana Kaplale (COMSERVA : Jurnal Penelitian dan Pengabdian Masyarakat, 2023)
This research was conducted to be able to analyze the level of income and feasibility of the sago plate business in Siri Sori Serani village. The samples taken in this study were 30 respondents using a simple random sampling method. The analytical method used in this study uses qualitative analysis obtained from primary data and secondary data. The results of this study explain that the average income of plate sago entrepreneurs earned by respondents is Rp. 626.375.833 per year. Even though the existing 30 plate sago entrepreneurs have R/C and B/C values > 1, the plate sago entrepreneur business in Siri-sori Serani Village, East Saparua District has experienced profits and can be said to be feasible for development.